The share of investments in gold and oil using the example of selected European stock exchanges-: A comparative analysis - Marcin Potrykus (Cogent Economics & Finance, 2021)
In this article, optimal investment portfolios with minimal risk and maximum efficiency were calculated. The portfolios were designated for ten selected European stock exchanges, based on the listings of the twenty largest companies in each of those markets. All calculations were made based on company shares only, company shares and investments in gold, shares of companies and investments in crude oil as well as shares of companies and investments in gold and crude oil. The research hypothesis tested in the study is: The share of alternative investments in the investment portfolio does not depend on the stock exchange, but it differs depending on the length of the estimation window used. The study showed that for most exchanges there were statistically significant differences for the distribution of the determined weight for alternative investments. However, it was noted that the longer the estimation window, the greater the number of exchanges with no differences in the distributions of that weight. In addition, for portfolios with minimal risk, there were larger differences between the designated weights of alternative investments than for the same portfolios, which were determined based on maximizing efficiency. It was also found that the longer the estimation window, the higher the efficiency of the designated portfolios. Moreover, the investment in gold had an average weight, in four-element portfolios with a minimum risk, greater than 60%. Oil investment in the same portfolios had an average weight of 28%.
Keywords: G11; G15; 330; investment in crude oil; investment in gold; maximum efficiency; minimal risk; optimal portfolio